Morphological diversity of northeastern fat-tailed and northwestern thin-tailed indigenous sheep breeds of Ethiopia - Deribe, B.; Beyene, D.; Dagne, K.; Getachew, T.; Gizaw, Solomon; Abebe, A. (Elsevier, 2021)
Characterization of indigenous sheep breeds using morphological traits is essential for designing rational conservation and improvement strategies. This study was conducted to check the morphological diversity of three fat-tailed and three thin-tailed indigenous sheep breeds of Ethiopia. The phenotypic traits such as live body weight and linear body measurements (body length, wither height, chest girth, chest depth, rump height, rump length, ear length, tail length, and pelvic width) were measured and used for analysis. The statistical analysis was done using different procedures of SAS 9.4. Analysis of variance showed significant variation between breeds. Multivariate analyses clearly assigned the studied sheep breeds into distinct populations. Mahalanobis distance showed significant (p < 0.01) difference between breeds. The present morphometric information obtained could support future decision-making on the management, conservation, and improvement of the studied sheep genetic resources.